X-ray spectroscopy station for sample characterization at ELI Beamlines - Zymaková, A; Precek, M; Picchiotti, A; Błachucki, W; Zymak, I; Szlachetko, J; Vankó, G; Németh, Z; Sá, J; Wiste, T; Andreasson, J (Scientific reports, 2023)
X-ray spectroscopy is a demanded tool across multiple user communities. Here we report on a new station for X-ray emission spectroscopy at the Extreme Light Infrastructure Beamlines Facility. The instrument utilizes the von Hamos geometry and works with a number of different sample types, notably including liquid systems. We demonstrate a simple and reliable method for source position control using two cameras. This approach addresses energy calibration dependence on sample position, which is a characteristic source of measurement uncertainty for wavelength dispersive spectrometers in XES arrangement. We also present a straightforward procedure for energy calibration of liquid and powder samples to a thin film reference. The developed instrumentation enabled us to perform the first experimental determination of the Kα lines of liquidized K3Fe(CN)6 as well as powdered and liquidized FeNH4(SO4)2. Finally, we report on proof-of-principle use of a colliding jet liquid sample delivery system in an XES experiment.